2010
DOI: 10.1254/jphs.09r11fm
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers in Gut Nutrient Sensor Research: Prophylactic Effect of Glutamine Against Helicobacter pylori–Induced Gastric Diseases in Mongolian Gerbils

Abstract: Abstract. Ammonia is one of the important toxins produced by Helicobacter pylori (H. pylori), the major cause of peptic ulcer diseases. We examined whether glutamine or marzulene (a gastroprotective drug containing 1% sodium azulene and 99% glutamine) protects the gastric mucosa against H. pylori in vivo and investigated the mechanism underlying glutamine-induced mucosal protection against ammonia in gastric epithelial cells in vitro. Mongolian gerbils were fed for 3 months with a diet containing glutamine (2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…We previously reported that both glutamine and MSG protected gastric epithelial cells against ammonia-induced cell death (5), and indeed, they were effective against H. pylori-induced diseases in vivo (6). Akiba et al (7,8) recently reported that MSG protected the duodenal mucosa against acid by enhancing the secretion of mucus/ bicarbonate, probably mediated by multiple glutamate receptors and suggested the importance of the chemosensing system to the duodenal mucosal defense.…”
Section: Introductionmentioning
confidence: 95%
“…We previously reported that both glutamine and MSG protected gastric epithelial cells against ammonia-induced cell death (5), and indeed, they were effective against H. pylori-induced diseases in vivo (6). Akiba et al (7,8) recently reported that MSG protected the duodenal mucosa against acid by enhancing the secretion of mucus/ bicarbonate, probably mediated by multiple glutamate receptors and suggested the importance of the chemosensing system to the duodenal mucosal defense.…”
Section: Introductionmentioning
confidence: 95%
“…Alternatively, it was suggested that A/A accelerates the conversion of glutamine to glutamate by glutamine synthetase, which depletes cells of ATP and reduces cell viability 17 . It is not fully understood why the viability of many cancer-derived epithelial cells is not affected by A/A when compared to non-transformed cells incubated with the same dose and time 1820 . Thus, we asked whether specific mechanisms exist to render non-transformed epithelial cells susceptible to ammonia cytotoxicity that are modified in gastric cancer.…”
Section: Background and Aimsmentioning
confidence: 99%
“…The antioxidant properties of L -glutamine have been claimed to be useful in the treatment of peptic ulcer disease in animal Case Report studies as well in very few human studies. Only a few animal studies have been conducted so far to investigate the role L-glutamine in the treatment of H. pylori infections and it was found to be positive, yet human trials have not been done in large scale [10]. As evidence says, glutamine helps in reducing the accumulation of ammonia in gastric tissue and cells as well it helps in reducing the oxidative free radicals in gastric tissue thereby controlling the changes induced by H. pylori infection in gastric epithelial cells [9].…”
Section: Discussionmentioning
confidence: 99%